Intertemporal Dynamics of Public Financing for Universal Health Coverage : Accounting for Fiscal Space Across Countries - Tandon, Ajay; Cain, Jewelwayne; Kurowski, Christoph; Postolovska, Iryna (World Bank, Washington, DC, 2019)
As countries undergo their health financing transitions, moving away from external and out-of-pocket (OOP) financing toward domestically sourced public financing, the issue of fiscal space – that is, of finding ways to increase public financing in an efficient, equitable, and sustainable manner -- is front and center in the policy dialogue around universal health coverage (UHC). Although how money is expended is just as critical as the overall resource envelope, we analyze changes in per capita public financing for health in real terms, a proxy for realized fiscal space, within and across 151 countries over time. This allows for an assessment not just of trends in public financing for health but also of contributions from three macro-fiscal drivers -- economic growth, changes in aggregate public spending, and reprioritization for health -- exploiting a macroeconomic identity that captures the relationship between these factors. Analysis of data from 2000 to 2015 shows per capita public financing for health in low- and middle-income countries increased by 5.0 percent per year on average: up from US$60 (2.2 percent of GDP) in 2000 to US$117 (2.8 percent of gross domestic product [GDP]) in 2015. Some of the largest increases were in countries in the Europe and Central Asia (ECA) and East Asia and Pacific (EAP) regions. At 3.1 percent per year, annual growth in public financing for health was lower among high-income countries, albeit from a much higher baseline in 2000. Increases in on-budget external financing comprised most of the changes among low-income countries, whereas domestic government revenues dominated changes in composition of public financing among lower- and upper-middle-income countries. Public financing increased at a faster rate than OOP sources for health in most regions except for South Asia. Although there are important country-specific differences, it is notable that more than half of the increase in public financing for health was due to economic growth alone. For the remainder of the increase, aggregate public spending contributed more than reprioritization across low and lower-middle-income countries, whereas the reverse was true in high-income countries. One key point of note from the landscaping exercise summarized in the paper is the diversity of growth trajectories across countries and, especially, the volatility in trends over time. The implications are clear: capturing public financing with a single growth rate is not the best metric to characterize country experiences, many of which are punctuated by episodes wherein trends are flat or have varying degrees of growth rates (positive or negative). Although country context matters, the importance of economic growth for public financing for health underscores the critical need to situate, integrate, leverage, and proactively manage health financing reforms within a country’s overall macro-fiscal context and to assess different pillars of fiscal space holistically.